The Effects of Group Identity on Pro-environmental Behavioral Norms in China: Evidence From an Experiment - Wan, Qinjuan; Deng, Hongping (Frontiers in Psychology, 2022)
This study experimentally evaluates the effects of group identity primed by property rights on pro-environmental behaviors (PEB) and social norms in an urban Chinese environment. The research in this paper expands the research perspective and method of domestic waste management and provides a theoretical basis for the establishment of a long-term mechanism of environmental treatment. We used two simple binary choice tasks that test the PEB and environmental types of individuals. This is one of the earliest tests for group identity and social norms in pro-environmental examinations in Chinese people. Our results reveal that (i) publicity and education have a significant positive effect on the development of individual and group pro-environmental behavioral norms; (ii) housing ownership has no differentiating effect on individual environmental behavior; and (iii) the development of social norms of pro-environmental behavior varies according to group conditions, which, in turn, determines individual environmental behavioral choices and types of environmental behavior. The results also suggest that PEB may be shaped and norms may be built by group conditions rather than group identity.